THE VESSELS INVOLVED IN HYDROSTATIC TRANSUDATION - McMaster, Philip D. (The Rockefeller University Press, 1932)
The gradient of permeability which exists along the cutaneous capillaries and venules is accentuated and broadened in scope by increasing the venous pressure moderately. Under such circumstances transudation leading to edema takes place most abundantly from the venules. The permeability of the portion of the capillary web that is near the arterioles increases only when the venous pressure rises so high as to approximate that in the arteries. Under such circumstances the gradient of permeability along the small vessels disappears, the capillaries and venules everywhere leaking fluid. The character of the vital staining developing under such circumstances indicates, like the evidence of previous work, that the cause for the gradient is to be sought in a structural differentiation.